Analysis of Factors that Influence Profit Persistency and Accural Quality (Universitas Negeri Semarang, 2022)
The purpose of this study was to examine the effect of managerial ability on earnings persistence and quality of accruals with managerial ownership as a moderating variable. The population in this study used property, real estate, and building construction sector companies listed on the Indonesia Stock Exchange for the period 2014-2018, the research sample was obtained by using the purposive random sampling method, a total of 155 data. The analytical technique used regression analysis with a moderation model. Based on the results of the study, it was found that managerial ability had a significant positive effect on earnings persistence and accrual quality. This study also succeeded in proving that managerial ownership was able to strengthen the relationship between earnings persistence and accrual quality, with managerial ownership they can predict future profits and utilize company resources, thus enabling managers to manage the company better and increase earnings persistence which will make the company's profits higher quality. This study contributed to providing evidence that managerial ability had a significant positive effect on earnings persistence and accrual quality, and proved that managerial ownership was able to strengthen the relationship between earnings persistence and accrual quality in managing the company.